Abnormal Vestibular–Ocular Reflexes in Children With Cortical Visual Impairment. Issue 4 (December 2021) - Mansukhani, Sasha A.; Ho, Mai-Lan; Brodsky, Michael C.
Abstract : Background: To determine whether the vestibular–ocular reflexes (VORs) can be affected by central nervous system injury in children with cortical visual impairment (CVI). Methods: Retrospective case series. Twenty consecutive children with CVI who presented to a pediatric ophthalmology practice over an 18-month period were included in the study. Horizontal and vertical VORs were assessed by a pediatric neuro-ophthalmologist using the standard doll's head maneuver. MRI studies were independently reviewed by a pediatric neuroradiologist in a masked fashion. The main outcome measures were the integrity of the VORs and the presence of brainstem abnormalities on MRI. Results: VORs were found to be absent or severely impaired in 13/20 (65%) children with CVI. More surprisingly, the doll's head maneuver failed to substantially overcome the deviated eye position in 8/13 (62%) children with conjugate gaze deviations. Reduced brainstem size and signal abnormalities were found in 4/7 children with normal VORs and in 9/13 children with abnormal VORs ( P = 0.6), showing noncorrelation with the integrity of the VOR. Conclusion: VORs are commonly impaired in children with CVI. This ocular motor deficit reflects the diffuse cortical and subcortical injury that often accompanies perinatal injury to the developing brain. Consequently, these children may lack important visual compensatory mechanisms to stabilize gaze during head movements. This knowledge can help in planning visual rehabilitation.